Teacher Readiness for Digital Transformation - Turrohmah, Hamimah; Suryanto, Suryanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The acceleration of digitalization in the field of education during the pandemic requires teachers to be quick to adapt. This study aims to describe teacher readiness in the form of mental readiness, self- readiness, and intelligence readiness to face digital transformation in terms of internal and external factors. The research methodology used is descriptive qualitative with data collection techniques, namely observation, interviews, and documentation conducted to six teachers from various school levels in Surabaya. The results of this study indicate that the readiness of teachers in the form of mental readiness, self, and intelligence to face digital transformation is good. However, there are obstacles in carrying out teacher activities using digital devices and media such as virtual media, web- based learning platforms, and the use of IoT (Internet of Things) caused by low adaptability. In overcoming this, the school's efforts are to provide digital literacy supplies and provide adequate digital technology. It is suggested that there is a need for a peer-to-peer pair learning program to speed up the adaptation process.